THE EFFECT OF IMPLEMENTING GCG (GOOD CORPORATE GOVERNANCE), WITH GGE (GREEN-GROWTH ECONOMY) AS A MODERATING VARIABLE OF FINANCIAL PERFORMANCE ON INCREASING ECONOMIC INCOME THROUGH GDP/GNP POST-TOWARDS THE NEW NORMAL - Prihatiningsih, Margaretha; Subagyo, Yusup Hari; Sibarani, Elisabeth Francisca; Paska, Intan; Ikko, Felix (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Research with the title: "The Effect of Implementing GCG (Good Corporate Governance), With GGE (Green Grouwth Economy) as a Moderating Variable of Financial Performance on the GNP/GDP of Development Board Companies whose Shares are Listed on the BEI (Indonesian Stock Exchange) for the 2020-2022 Observation Period aims to Knowing How the Implementation of GCG Influences Financial Performance CAR Liquidity, DAR & DER Solvency, NPM Profitability & ROA Profitability, ROE & ROI and Tobinsq can increase GDP/GNP through the moderation variable GGE can spur an increase in GDP/GNP for Development Board Companies whose shares are listed on BEI. Implementation of GCG (Good Corporate Governance), with GGE (Green Grouwth Economy) as a moderating variable will spur GDP/GNP. The methodology used is the Quantitative Method with Multiple Correlation Regression Test, Anova TEST F & T-test and R Quadrate to calculate and test data on variables X & Y from the population taken in this research, namely all companies whose shares are listed on the BEI Development Board (Period 2020 to 2023 there are 372 companies). Meanwhile, the sample of 80 companies met the sampling criteria and covered all the variables studied and had Financial Reports for 3 consecutive years, with a complete Report Development Board Annual Report for 17 companies. Based on MRA analysis, the following results were obtained: (1) The influence of ROI, & CAR on GNP (Y1) through GGE (Z1) with a significant value of 0.036; 0.024 is below 0.05. So ROI & CAR through GGE (Z1) are able to influence GNP (Y1), which means the hypothesis is accepted. (2) The influence of DER, & Tobinsq on GNP (Y1) through GGE (Z1) shows a significant value of 0.024, 0.027 below 0.05. So DER & Tobin's Q through GGE (Z1) is able to influence GNP (Y1), which means the hypothesis is accepted. Results of Analysis 2: (1) The influence of ROA, CAR, & Tobins Q on GNP (Y1) through GCG (Z1) The t calculated regression value of ROA, CAR, & Tobinsq with a significant value of 0.001; 0.036; 0.000 under 0.05. So ROA, CAR & Tobinsq through GCG (Z1) are able to influence GNP (Y1) which means it is acceptable. Based on the results of Analysis 3 as follows: (1) Effect of Tobin's Q, ROA; ROI, DER to GDP (Y2) via GGE (Z1) as a mediating variable - with a significant value of 0.827; above 0.05; while 0.001; 0.026; 0.011; & 0.000 below 0.05. So Tobin's Q; ROA; ROI; DER via GGE (Z1) is unable to influence GDP (Y2) which means it is rejected, while var ROA, ROI & DER is accepted. Based on the results of the MRA 5 analysis as follows: (1) ROA, ROI through GGE (Z2) is able to influence GDP (Y2) which means it is acceptable. (2) Based on Analysis Results (6) as follows: (1) Influence of ROA; ROI; DER; TobinsQ; ROE, on GDP (Y2) through GGE (Z2) as a mediating variable can indirectly influence GDP (Y2), which means it is acceptable. Keywords: GCG, GGE, Moderating Variables, MRA, Financial Performance Liquidity, Solvency, Profitability, Profitability, GDP/GNP.